Immunoprophylaxis of infectious diseases in premature infants - Alexander A. Baranov; Leyla S. Namazova-Baranova; Irina A. Belyaeva; Irina V. Davydova; Nikolay N. Volodin; Elena A. Vishneva; Marina V. Fedoseenko; Liliia R. Selimzianova (Union of pediatricians of Russia, 2018)
Premature infants are especially in need of timely and effective specific immunoprophylaxis due to their vulnerability to infectious diseases. The article describes the basic principles for vaccination of premature infants used in healthcare by the leading countries of the world. Based on the results of clinical trials, the peculiarities of the vaccination schedule for certain infections have been determined, the specific features of the course of the post-vaccinal period have been described. The operating procedures for active immunoprophylaxis of various types of infections have been explained in detail depending on the pathology and the therapy being performed. The article uses the key points of the recommended practices for prevention of the main controlled types of infections developed by the professional association of pediatricians 'Union of Pediatricians of Russia' and approved by the Ministry of Healthcare of the Russian Federation.